Using Airborne Laser Scanning Data to Assess the State Historical Garden Complexes - Anna Dudzińska; Barbara Szpakowska (Barometr Regionalny)
The aim of the study was to assess the possibility of applying GIS analysis for investigations into the state of preservation of a baroque garden complex. The article presents a method based on Airborne Laser Scanning data (LIDAR) which can be used for analysis of revalorization of historical garden complexes. The research was conducted in a rural park in Siemczyno, Zachodniopomorskie Voivodship, Poland. The analysis was made by means of the ENVI and ArcMap programs. The article presents an analysis of the terrain microstructure, which was used for assessment of changes in the terrain. It is a significant element used for planning public space. The research results were compared with the park inventory data of 1973. The research proved that LIDAR data analysis could be used for assessment of the state of preservation of historical garden complexes. It might also be used for preparation of park registration documentation or revalorization plans.